Educação nos espaços de privação de liberdade em Goiás: tensões, contradições e desafios - Silva, Lucas Lourenço (2022)
This research analyzes the education policies in prisons performed in Brazil in the last two decades, with special attention to its materialization in the state of Goiás. The guiding question of the analysis is to comprehend if the legal regulations and their effectiveness are contributing to the guarantee of the right to education of people that are deprived of liberty, starting from the more specific analysis of the effectiveness of the State Educational Plan in Prisons in Goiás (PEEPGO, 2012-2015). The research uses the contributions of Stephen Ball in the analysis of the policy cycle, this being a theoretical reference marker. It is anchored, also, in the theories of Foucault, Goffman, Berger, P., and Berber, B. to think of the prison as a social institution; and in the reflections of Julião for the comprehension of the context of the education policies in Brazil. The theoretical and methodological frameworks assisted in the data analysis, registered in the official platforms of the National Survey of Penitentiary Information (Infopen), of the System of Information of the National Penitentiary Department (Sisdepen), of the National Penitentiary Department (Depen), and of the Secretariat of Education and Culture of the State of Goiás (Seduc-GO), priority sources of investigation. For purposes of research exposure, in addition to the Introduction and Final Considerations, this dissertation is composed of four other sections: the second section has a survey of works already performed with themes facing prison education, the context of international influences, and prison as an institution. The third section is dedicated to the study of the legislation of prison education. The fourth section has an analysis of the state plans of education in the prisons of the federal units, while the fifth section presents the study of the State Educational Plan in Prisons in Goiás (PEEPGO, 2012-2015). The research results demonstrate that, after the implementation of the PEEPs (2012-2014, and 2015-2017), there was no increase in the total enrollments in school education, because in 2012 there were 11% of Brazilian prisoners studying and, in 2017, this percentage fell to 9,6%. The information systems reveal that there was an increase of 276% in educational activities, considering also those that are not educational. In Goiás, the attendance stayed below 10% during the validity of the PEEPs, having an increase of 200% during the pandemic, during which the non-attendance classes were authorized (Reanp), which the prisoners performing individualized studies or being monitored by other prisoners. It is concluded that there is a exclusion of the people in situation of deprivation or liberty restriction to the educative processes in schools, having a makeup of data, with the oversizing of the offer in educational activities, but without the commitment with the social quality of basic education, a constitutional right in Brazil.